Production and Income Risk of RSPO Certified and Non-Certified Oil Palm Smallholders - Syahputra, Agung Rahmat; Nurkhoiry, Ratnawati; Amalia, Rizki; Prima Sani Nasution, Zulfi (Jurnal Penelitian Kelapa Sawit, 2024)
Palm oil plantations are often criticized for poor governance practices covering environmental, social, and economic aspects. Sustainability certification has emerged as a solution to these issues, offering assurances of sustainability in the supply chain to stakeholders, including smallholders. Without certification, smallholders face significant risks, including market volatility and production losses, which able to impact their income and the sustainability of their operations. This study aims to evaluate and compare production and income risks between certified and non-certified smallholders. Research method involves calculating the coefficient of variation to measure risk. Results show that certified smallholders face lower risks compared to non-certified smallholders, both in terms of production and income. This reflects better risk management, particularly in more efficient labor allocation and higher financial gains, despite higher costs. This success is inseparable from the support of the RSPO and cooperatives, which play a vital role in fulfilling the commitment to achieve the goals outlined in the Theory of Change (ToC).